The New Media in the 2008 U.S. Presidential Campaign: The New York Times Watches Its Back - Schudson, Michael (Javnost-The Public, 2009)
A reading of New York Times’ coverage of the 2008 presidential campaign demonstrates that America’s most influential newspaper paid a great deal of attention to the role of new media (and some old media – television, cable television, television advertising) in the campaign. As a kind of reader’s diary chronicling the Times’ account, this article finds that the news coverage emphasised a new intensity, a remarkable ubiquity, and a note of anarchism in the new communication media, enabling citizens with little connection to candidate or party power centres to at least briefly gain national notoriety in political news.